That Obscure Object of Desire: John Nash and the general theory of the second best (Revisiting the Year of Economics correspondence on the occasion of the untimely death of John and Alicia Nash on 23 May 2015). (3rd July 2016) - Ghiara, Abhay; Goulish, Matthew
Abstract : TheYear of Economics correspondence was an economics and performance letter-writing project guided by the simple idea that Matthew would attempt to formulate an economics question in each letter to Abhay and that Abhay would attempt to answer that question. TheYear of Economics project began in May 2003 and was originally meant to last one year. After the first year, Matthew and Abhay decided to continue the project, calling itFour More Years of Economics . Although the project ended in May 2007 Matthew and Abhay continue to write economics letters to each other as events unfold related to their letters, such as a site visit to Adam Smith's grave in Edinburgh and another to Gandhi's Sabarmati Ashram (from where he launched the Salt Satyagraha). The occasion for this piece, coincident with thisPerformance Research call, is the death of John and Alicia Nash on 23 May 2015, and some thoughts that Matthew and Abhay wanted to commit to writing in the aftermath of that accident. This piece consists of two letters from theYear of Economics correspondence and two postscripts.